The Effect of Providing HOTS (Higher Order Thinking Skills) Based Questions on Students' Critical Thinking Ability in Islamic Religious Education Subjects at SMP Negeri 10 Palembang - Zulhijra Zulhijra; Nevy Nahrisyah; Seli Sugiarto; Aliffia Putri Azzahra (Universitas Muhammadiyah Enrekang, 2024)
This study explores and analyses the impact of giving questions designed based on the principles of higher-order thinking Skills (HOTS) on students' critical thinking skills in Islamic Religious Education (PAI) subjects. In this study, the method used is quantitative, where the data collected is in the form of numbers obtained from the respondents involved. Based on the results of the analysis conducted, it was found that there was no significant effect regarding the provision of HOTS-based questions and students' critical thinking skills in the context of Islamic Religious Education (PAI) learning. In other words, it can be concluded that although HOTS questions are designed to improve critical thinking skills, the results show that the administration of these questions does not significantly impact students' critical thinking skills. The findings of this study indicate the need for further studies on other factors that may affect students' critical thinking skills in this subject. Therefore, further research is essential to understand more comprehensively the aspects that can contribute to improving students' critical thinking skills.